2020
DOI: 10.1007/s40194-020-00894-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of grinding weld treatment methods using effective notch stresses

Abstract: An experimental and numerical research program is executed to investigate the fatigue lifetime increase due to grinding-type post-weld treatment method. Plate edge gusset, longitudinal attachment and T-type joint specimens are investigated using fatigue test results, numerical models and mathematical statistical tools. The favourable impact of grinding on fatigue lifetime of the analysed joints is commonly known for researchers. However, considering the lifetime increasing effect is mainly based on experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…In order to ensure a small level of additional conservatism, the results of specimens (four test series) with thickness t > 25 mm were not corrected for thickness effects; however, including a thickness correction would not affect the correlation significantly. Thus, the results by Mecséri and Kövesdi [13] and Hanzawa et al [19] could not be confirmed in this study. It can be concluded that fatigue strength improvement by means of grinding is independent of the specimen thickness.…”
Section: Parent Materials Strength and Specimen Sizecontrasting
confidence: 75%
See 2 more Smart Citations
“…In order to ensure a small level of additional conservatism, the results of specimens (four test series) with thickness t > 25 mm were not corrected for thickness effects; however, including a thickness correction would not affect the correlation significantly. Thus, the results by Mecséri and Kövesdi [13] and Hanzawa et al [19] could not be confirmed in this study. It can be concluded that fatigue strength improvement by means of grinding is independent of the specimen thickness.…”
Section: Parent Materials Strength and Specimen Sizecontrasting
confidence: 75%
“…[18]. Furthermore, the plate thickness is expected to affects the fatigue strength improvement after grinding, see Mecséri and Kövesdi [13] and Hanzawa et al [19]. In both studies, a higher fatigue strength after grinding was measured for the thicker steel plates; however, the number of performed tests is too small to draw conclusions from these comparisons.…”
Section: Fig 2 Basic Principle Of Weld Toe Grinding and Weld Profilin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue performance of the joints was evaluated numerically based on the prediction of fatigue crack initiation and propagation lives, where the bead geometry, angular distortion and changes in material properties by weld heat were considered [9][10][11][12][13][14] . The FE 1.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…Fatigue failure of weld structures is often initiated around the welded parts due to a series of factors, such as stress concentration caused by the geometry of the welding bead, changes in material properties by heat input, residual stresses and deformations. On the other hand, grinding, TIG treatment, peening, etc., are available to improve the fatigue strength of welded joints [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Some of those methods have been standardized in JSSC 3) as improving methods to enhance the fatigue performance of joints.…”
Section: Introductionmentioning
confidence: 99%